Viking Age Swords from Telemark, Norway An Integrated Technical and Archaeological Investigation - Martens, Irmelin (Norske Oldfunn, 2021)
Viking Age Swords from Telemark, Norway. An Integrated Technical and Archaeological Investigation provides a metallographic analysis of 21 Viking Age swords found in the county Telemark in southeastern Norway. The book is the result of a collaboration between archaeologist Irmelin Martens and chemist Eva Elisabeth Astrup. 220 swords have been found in Telemark, and they are a mix of domestic Norwegian and imported European types. The difficulties in determining which ones were made in Norway are complicated by and closely connected to the specific skills Norwegian blacksmiths had mastered with respect to both blade construction and inlay decoration. The metallographic investigations revealed five construction types for sword blades, of which four, requiring different technical levels of smithing, may well have been mastered by Norwegian blacksmiths at that time. Combined with x-ray radiographic studies, the metallographic investigations indicate that new techniques were indeed introduced and disseminated among weaponsmiths during the Viking Age. The findings are also probably representative for the combined total of more than 3000 swords found in all areas of the country. The majority are domestic types, and their great number obviously reflects the organization of sword production and influenced blacksmiths' social standing.